Deconstruction J. Derrida and Hermeneutics - Diah Ayu Anggraini; Amril (At Turots: Jurnal Pendidikan Islam, 2026)
This article discusses the relationship between Jacques Derrida's deconstruction theory and hermeneutics in the context of modern epistemology. Both approaches seek to reject the traditional view of meaning as singular, fixed, and objective. Derrida, through his deconstruction, reveals that meaning is always relative, contextual, and constantly changing, while hermeneutics emphasizes the importance of the dialogical interpretation process between the text, the reader, and the socio-cultural context. The integration of deconstruction and hermeneutics produces a more open, critical, and reflective epistemological paradigm. This approach asserts that knowledge is not a definitive end result, but a dynamic process that can always be reinterpreted according to context and human experience. Thus, deconstruction and hermeneutics play an important role in expanding the horizon of scientific understanding and enriching cross-disciplinary interpretive methods. In addition, the application of Derrida's thought and hermeneutics has great relevance in Islamic studies and the humanities. Both encourage reinterpretation of religious and social texts in a more critical and contextual manner, thereby opening space for the emergence of a more inclusive, progressive, and adaptive scientific understanding in response to the times.